Local Policy Synergy with Law Number 6 of 2014 Concerning Village in the Nagari Government in West Sumatera Indonesia - Dasman Lanin; Hasbullah Malau; Boni Saputra (Journal of Advanced Research in Social Sciences and Humanities, 2021)
Aim: The Indonesian practice of decentralization is based on centralistic bureaucratic thinking, which ensures that all aspects of government, including governance structures, politics, institutions, law, and finance, are applied consistently across all levels of government. But there are significant differences between regions, so standardization is impossible. Reasons for this include the potential for conflict resulting from divergent perspectives on history, regional rights, religion, language, culture, politics, geography, economy, and ethnicity. The decentralization strategy is meant to create harmony between traditional knowledge and the Nagari Ministry’s efforts to implement Community Law Number 6 of 2014. Methodology: For this study, we opted for a qualitative, descriptive approach. Purposive sampling was used to select participants in the villages of Nagari Kapau, Nagari Minangkabau, Nagari Mahakarya, and Nagari Anduring in Indonesia’s West Sumatra Province. In-depth interviews, surveys, and written research records were all used to compile the data. The data’s reliability was checked using data aggregation methods in this probe. Findings: The findings show that while the concepts of both the bottom-up and top-down Nagari governance model and Law Number 6 of 2014 can be accommodated in theory, in practice, the Mixing government model presents significant challenges. Implications/Novel Contribution: This research supports the idea that Nagari public administration can easily incorporate conventional wisdom from the region. This research has also recommended that future scholars think about the bottom-up government model and the top-down government model that can create harmony between the interests of the community or citizens of the village and a government that is structured from the top (top-down) through Law number 6 of 2014 and other legislation. Many nations make similar attempts, and essential takeaways from this research could be applied to governments in the same region.